Comparative Efficacy and Safety of Four Different Spontaneous Breathing Trials for Weaning From Mechanical Ventilation: A Systematic Review and Network Meta-Analysis - Yi, Li-Juan; Tian, Xu; Chen, Min; Lei, Jin-Mei; Xiao, Na; Jiménez-Herrera, Maria F. (Frontiers in Medicine, 2021)
Background: Spontaneous breathing trial (SBT) has been used to predict the optimal time of weaning from ventilator. However, it remains controversial which trial should be preferentially selected. We aimed to compare and rank four common SBT modes including automatic tube compensation (ATC), pressure support ventilation (PSV), continuous positive airway pressure (CPAP) and T-piece among critically ill patients receiving mechanical ventilation (MV). Methods: We searched PubMed, EMBASE and the Cochrane Central Register of Controlled Trials (CENTRAL) to identify studies investigated the comparative efficacy and safety of at least two SBT strategies among critically ill patients up to May 17, 2020. We estimated the surface under the cumulative ranking curve (SUCRA) to rank SBT techniques, and determined the certainty of evidence using the Grading of Recommendations Assessment, Development and Evaluation method. Primary outcome was weaning success. Secondary outcomes were reintubation, SBT success, duration of acute care and intensive care unit (ICU) mortality. Statistical analysis was conducted by using RevMan 5.4, Stata and R software. Results: We enrolled 24 trials finally. Extubation success rate was significantly higher in ATC than that in T-piece (OR, 0.28; 95% CI, 0.13 to 0.64) or PSV (OR, 0.53; 95% CI, 0.32 to 0.88). For SBT success, ATC was better than other SBT techniques, with a pooled OR ranging from 0.17 to 0.42. For reintubation rate, CPAP was worse than T-piece (OR, 2.76; 95% CI, 1.08 to 7.06). No significant difference was detected between SBT modes in ICU or long-term weaning unit (LWU) length of stay. Similar result was also found for ICU mortality between PSV and T-piece. Majority direct results were confirmed by network meta-analysis. Besides, ATC ranks at the first, first and fourth place with a SUCRA of 91.7%, 99.7%, and 39.9%, respectively in increasing weaning success and SBT success and in prolonging ICU or LWU length of stay among four SBT strategies. The confidences in evidences were rated as low for most comparisons. Conclusion: ATC seems to be the optimal choice of predicting successful weaning from ventilator among critically ill patients. However, RCTs with high quality are needed to further establish these findings.